Identification of Factors Affecting Ethical Internal Auditing - Jamshidi, Hamed; Hajiha, Zohreh; Salehi, Mehdi (Business, Marketing, and Finance Open, 2024)
This study aims to investigate the ethical practices of internal auditing and the factors influencing auditors' judgments. Specifically, it explores the impact of legal, behavioral, professional, and committee-related factors on the quality of internal auditing and auditors' decision-making processes. The research adopted a descriptive analysis method, utilizing a survey-based approach. A sample of 384 auditors from auditing firms and organizations across Iran participated in the study. Data was collected using a structured questionnaire and analyzed through statistical methods to identify relationships between various factors and ethical decision-making in internal auditing. The study found that behavioral factors, such as the auditors' experience and gender, had a significant impact on ethical decision-making. Legal factors, particularly proficiency in using information systems and understanding relevant laws and regulations, were found to enhance auditors' judgment quality. Additionally, professional factors, including a comprehensive understanding of management’s objectives and organizational goals, were crucial for auditors to provide effective judgments. The findings also indicated that committee-related factors, such as continuous training in information systems, improved auditors' ability to make informed decisions. The research concludes that ethical decision-making in internal auditing is influenced by a combination of behavioral, legal, professional, and committee-related factors. It emphasizes the importance of continuous professional development, ethical standards, and understanding the organizational context to enhance the quality and effectiveness of internal audits. Further research is needed to explore these relationships in other organizational settings and to investigate additional variables that might affect auditors' ethical decision-making.